Lithuanian Poles Values in the Poetic Texts of Dr. Gabriel Jan Mincewicz - Fedorowicz, Irena; Geben, Kinga (Vilnius University Open Series, 2020)
The current paper presents an overview of the poetic texts of Gabriel Jan Mincewicz (1938–2016) (PhD in the field of humanities, branch of theology). Merits of Gabriel Jan Mincewicz as the director of the song and dance ensemble “Wileńszczyzna” are emphasized. The poetic works of G. J. Mincewicz were divided into several thematic groups, among them the cultural determinants of the Polish identity and the linguistic image of the homeland were analyzed. The works were discussed in the sacred, historical, social, and linguistic contexts. The article emphasizes as well the social impact that G. J. Mincewicz’s songs have on the society of Vilnius region.